Patients' thoughts on patient-retained medical records - A.L. Norden; G.J.O. Marincowitz; G.S. Fehrsen (South African Family Practice)
Background: Patient-retained cards and, later, patient-retained booklets were introduced in an effort to improve continuity of care in a primary care setting at Tzaneen Clinic in the Greater Tzaneen Municipality of Limpopo Province, South Africa. Previously, the only continuity was maintained through a clinic-retained patient register, referral letters or information the patients provided themselves. The Patient-Retained Booklet of Lesotho provided motivation for this project.